THE PECULIARITIES OF MANUFACTURING PROCESS GLOBAL FRAGMENTATION IN THE MODERN BUSINESS (Globalization and Business, 2018)
The paper considers the main theoretical approaches to understanding global fragmentation of manufacturing processand analyzes their role in the modern International business. It is emphasized that in view of the growing political and economic importance of manufacturing process global fragmentation, today this phenomenon is in the focus of many countries and international institutions.There are analyzed mechanisms of coordination, structure, the importance of individual points and the effectiveness of possible positions of the company inglobal fragmentation of manufacturing process.